1995
DOI: 10.1073/pnas.92.14.6625
|View full text |Cite
|
Sign up to set email alerts
|

Disparate responses to oxidative stress in saprophytic and pathogenic mycobacteria.

Abstract: To persist in macrophages and in granulomatous caseous lesions, pathogenic mycobacteria must be equipped to withstand the action of toxic oxygen metabolites. In Gram-negative bacteria, the OxyR protein is a critical component of the oxidative stress response. OxyR is both a sensor of reactive oxygen species and a transcriptional activator, inducing expression of detoxifying enzymes such as catalase/hydroperoxidase and alkyl hydroperoxidase. We have characterized the responses of various mycobacteria to hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
161
0
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(169 citation statements)
references
References 13 publications
4
161
0
4
Order By: Relevance
“…On the bacterial side, M. tuberculosis virulence has been associated with its initial survival within macrophages and resistance to reactive oxygen and nitrogen intermediates (ROIs and RNIs) (5)(6)(7)(8). Tubercle bacilli demonstrate inducible responses to oxidative stresses, and several M. tuberculosis genes, including katG (catalase peroxidase), ahpC (alkylhydroperoxide reductase), and sodA and sodC (superoxide dismutases) have been implicated in protection from the macrophage oxidative burst (9)(10)(11).…”
mentioning
confidence: 99%
“…On the bacterial side, M. tuberculosis virulence has been associated with its initial survival within macrophages and resistance to reactive oxygen and nitrogen intermediates (ROIs and RNIs) (5)(6)(7)(8). Tubercle bacilli demonstrate inducible responses to oxidative stresses, and several M. tuberculosis genes, including katG (catalase peroxidase), ahpC (alkylhydroperoxide reductase), and sodA and sodC (superoxide dismutases) have been implicated in protection from the macrophage oxidative burst (9)(10)(11).…”
mentioning
confidence: 99%
“…Further evidence for this hypothesis is the genome sequence conservation between M. tuberculosis and M. bovis. In addition, a recent study suggested that molecules such as mycothiol may serve as partner molecules in the enzymatic cycle of the mycobacterial alkyl hydroperoxide reductase (AhpC) (27), an enzyme that has been shown to detoxify organic peroxides (24) and possibly H 2 O 2 (28). This enzyme has been implicated in the survival of INH resistant M. tuberculosis, as point mutations in the AhpC gene was associated with drug resistance (29) and its expression was shown to be up-regulated in M. tuberculosis drug resistant phenotypes (30).…”
Section: Discussionmentioning
confidence: 99%
“…2 (lane 2), was not detected under standard in vitro culture conditions. However, mRNA transcripts of this gene appeared in M. bovis BCG within 30 min after exposing the bacteria to a non-lethal dose of INH (MIC for INH in M. bovis Pasteur is 0.1 ug/ml in BACTEC) (24), as indicated in Fig. 2 (Rv1170), lane 3.…”
Section: In Silico Analysismentioning
confidence: 93%
“…This protective response of oxyR was evident in the saprophytic Mycobacterium smegmati but absent in the MTC and the Mycobacterium avium complex (MAC). However, homologues of the oxyR gene have been isolated from MTC and MAC (Sherman et al 1995). While the MAC oxyR appears intact, the oxyR homologue of MTC contains numerous deletions and frameshifts and probably does not encode a functional protein; it is referred to as a pseudogene (Sherman et al 1995).…”
mentioning
confidence: 99%
“…However, homologues of the oxyR gene have been isolated from MTC and MAC (Sherman et al 1995). While the MAC oxyR appears intact, the oxyR homologue of MTC contains numerous deletions and frameshifts and probably does not encode a functional protein; it is referred to as a pseudogene (Sherman et al 1995). Inasmuch as pseudogenes accumulate mutations at an increased rate compared with functional genes, Sreevatsan et al (1996Sreevatsan et al ( , 1997 described a polymorphic nucleotide located at position 285 of the oxyR pseudogene that differentiates M. bovis from other complex members.…”
mentioning
confidence: 99%